The Effect of Step Frequency Training on a Male Runner with Patellofemoral Pain - Shelley Payne; Katelyn Barrett; Joe Wilkins (Bowling Green State University, 2016)
Running is a very popular form of exercise. The most common site of injury for runners is the knee with patellofemoral pain being the most common complaint. Patellofemoral pain is described as pain around the patella that is worse with activities such as running, squatting, ascending or descending stairs, or sitting for long periods. Much of the recent work with the treatment of patellofemoral pain has involved strengthening of the hip musculature to reduce pain about the knee. However, the ability of these strengthening programs to change lower extremity mechanics or sustain long-term pain reduction has been unproven. More recently, researchers have started to examine the impact of step frequency modification on the forces encountered in the lower extremity, and specifically about the patellofemoral joint. The purpose of this study was to examine the short term effects of step frequency training in a recreational runner with PFP. Methods: This was a single-subject case study design. The subject completed a pre- and post-training assessment to determine the preferred step frequency. The subject also completed a Visual Analog Scale (VAS) and a Lower Extremity Functional Scale (LEFS). Results: After the initial evaluation, the subject completed training 2 times per week for 4 weeks using auditory feedback to increase their step frequency by 5% above their preferred step frequency. The subject experienced a decrease in pain as measured by the VAS and an increase in function as measured by the LEFS across the 4 week training. Discussion: Although the results of this case study may not be generalized, the positive findings support additional research to determine both the short and long-term effects of step frequency training on PFP.